Protection of Human Rights and Freedoms in the Administrative Proceedings of the European Union - Расторгуєв, Олександр Валерійович; Расторгуєв, О. В.; Расторгуев, Александр Валерьевич; Rastorhuiev, Oleksandr V.; Макушев, Петро Васильович; Макушев, П. В.; Макушев, Петр Васильевич; Makushev, Petro V.; Пухтецька, Алла Альбертівна; Пухтецька, А. А.; Пухтецкая, Алла Альбертовна; Pukhtetska, Alla A.; et al. (Hasanuddin University, 2021)
Since there is a problem of forming a system of modern doctrinal knowledge on protection in administrative proceedings by individuals of their rights violated in public relations, the topic under research becomes relevant. The justice in national administrative cases requires qualitative improvement taking into account European experience. The purpose of the research is to form a uniform judicial enforcement in the field of public relations, establish the rule of law, and provide fair justice. The methodological basis of this study is a set of general scientific (dialectical, analysis, and synthesis), as well as special legal (historical, comparative law, consideration and interpretation of legal norms, formal-logical) methods of scientific knowledge. The practical significance of the obtained results is that the formulated theoretical provisions, proposals and recommendations can be used: in research to conduct further research on the problems of administrative proceedings in Ukraine, ways and means of effective protection of subjective rights of individuals; in law-making for further improvement in accordance with European principles of national legislation; in the law enforcement practice of judges of administrative courts of Ukraine for consideration and resolution of public law disputes, in the protection of their rights in administrative judicial specialization by citizens and legal entities.

Оскільки існує проблема формування системи сучасних доктринальних знань щодо захисту в адміністративному судочинстві особами своїх прав, порушених у суспільних відносинах, тема дослідження стає актуальною. Правосуддя у національних адміністративних справах потребує якісного вдосконалення з урахуванням європейського досвіду. Метою дослідження є формування єдиного судового виконавчого органу у сфері суспільних відносин, встановлення верховенства права, забезпечення справедливого правосуддя. Методологічною основою даного дослідження є сукупність загальнонаукових (діалектичний, аналіз, синтез), а також спеціально-правових (історичне, порівняльне правознавство, розгляд і тлумачення правових норм, формально-логічні) методів наукового пізнання. Практичне значення одержаних результатів полягає в тому, що сформульовані теоретичні положення, пропозиції та рекомендації можуть бути використані: у дослідженні для проведення подальших досліджень проблем адміністративного судочинства в Україні, шляхів і засобів ефективного захисту суб’єктивних прав осіб; у законотворчості для подальшого вдосконалення відповідно до європейських принципів національного законодавства; у правозастосовчій практиці суддів адміністративних судів України з розгляду та вирішення публічно-правових спорів, у захисті громадянами та юридичними особами їх прав в адміністративно-судовій спеціалізації.
Rastorhuiev O. Protection of Human Rights and Freedoms in the Administrative Proceedings of the European Union / O. Rastorhuiev, P. Makushev, A. Pukhtetska, A. Hridochkin, I. Smaznova // Hasanuddin Law Review. – Vol. 7. – Iss. 3 - Hasanuddin University, 2021. – P. 210-225.
Keywords: administrative justice; case law; civil rights; European administrative space; human rights; адміністративне судочинство; судова практика; громадянські права; європейський адміністративний простір; права людини; Research Subject Categories::LAW/JURISPRUDENCE